Pendidikan Agama Kristen di Sekolah - Tulangouw, Maria Elisa (Educatio Christi, 2022)
This article begenned with the terminology of definition Christian Religious Education, function and the curriculum who used in the school. There are some problems about the teacher and their roles at the school. The aim of this article for sharing information about how we must facing the reality and to knowing the needed of teacher with students. Researcher using literature books and qualitative method approach. As part of an analyst the Christian Education in relation between teacher, student and also education in family. This article also talking about comparison between Christian Education in Government School and Christian School. Hopefully this article who talking about Christian Religious Education has impact into relation among teacher, students with family.